When culture meets sustainability - Gonçalves, A. (Socioecos: Climate change, sustainability and socio-ecological practices : Conference Proceedings, 2024)
Social change towards more sustainable lifestyles is not caused and implemented by normative directives and political decisions alone. Cultural production can act as a factor that promotes or prevents public awareness of the worldwide challenges we face today. On the one hand, high and popular artworks attract local and global audiences and impact the social imaginaries of many. On the other hand, what we call culture has a long-term effect. Culture constitutes accumulated resources, material or immaterial, which individuals inherit, use, change, add to, and transmit. When socially recognised and valued, the cultural elements handed down from generation to generation become heritage, linking the already-dead to the not-yet-born. This brief essay explores why culture matters for sustainability and how creative and artistic endeavours may sharpen people’s consciousness of their actions and aspirations, promote feelings of responsibility for the environment, and trigger civic agency in the face of a climate and ecological emergency. The argumentative framework draws from recent developments in the disciplinary subfields of the sociology of culture and the arts and the interdisciplinary field of cultural studies. These pages also approach the so-called ecological turn in the arts, demonstrating its plausibility through empirical analyses of examples from the plastic, visual, and performing arts that currently cover an array of environmental topics, from natural disasters to climate change, helping us cope with the precariousness of near and distant scenarios. All art pieces were selected from a single-case study conducted in Quinta do Pisão, a nature park on the outskirts of Cascais, a coastal town west of Lisbon, in Portugal. Three open-air art installations or interventions, part of the broad movement known as land art or environmental art, are briefly reviewed and contextualised. The findings, even if quite provisory and limited, reinforce the idea that environmentalism is already established within the art world. The ecological ethics of twenty-first-century artworks are, in fact, integral to their overall aesthetic value. However, further research is needed to understand how artworks may reach individuals and society and how their webs of significance can be bequeathed to future generations.